Rootstock performance and bud development evaluation to optimize Vitis vinifera production - Dias, Frederico Alcântara Novelli (2015)
Wine grapes are constrained to a narrow climatic range and consequently are especially sensitive to climate change, with potential effects on yield, quality and profitability. Researches to increase knowledge about reproductive development and new agriculture practices, and opening of new wine making areas are important to overcome climates limitations. In Brazilian southeast, a new management approach called double pruning allows the change of wine grape harvest season from wet summer to dry winter. Thus, the present thesis had as issue evaluation of different rootstocks on grapevine Syrah performance and wine quality in Brazilian southeast; and the validation of a new grapevine model, called Microvine, to winter bud development studies. A competition of ten rootstocks under Syrah was developed during two seasons in south of Minas Gerais state, Brazil. Rupestris du Lot and IAC 766 induced the highest pruning weight, while R110 and 161-49C showed the lowest vegetative development. The average yield per plant of two seasons identified Rupestris du Lot, IAC 766, 1045P and Kober 5BB as the most productive rootstocks. The more vigorous rootstocks did not affect negatively grape quality of Syrah under double pruning management. Syrah’ wine from productivity and vigorous rootstocks, ‘IAC 766’ and ‘Rupestris du Lot’, showed satisfactory wine phenolic composition and alcohol/acidity balance. The development of microvine winter bud was also evaluated along the proleptic axis based on microscopy and X-ray micro-tomography image methods. Microscopy accuracy was higher to assess phytomers and inflorescence primordia initiation within winter buds. Lignified buds, exhibited a maximum of 6 phytomers and 2 inflorescences primordia, inserted on the distal phytomers (4 to 6), similarly to grapevine. Primary bud length was highly correlated with the number of inflorescences primordia and phytomers. Therefore, further studies, in Brazilian southeast, involving only vigorous and productive rootstocks and the traditionally rootstocks used should be continued to described vine performance and wine quality on aged plants. The framework of phenotyping bud development set up in this work could identify critical points on plant development to increase vine production under double pruning management.